Factors Influencing the Incidence of Abortion at Imelda Pekerja Indonesia General Hospital in 2023 - Winda, Isra Nur; Nadapdap , Thomson P.; Fitria , Aida (Universitas Ibn Khaldun Bogor, 2025)
Incidence of Abortion at Imelda Pekerja Indonesia General Hospital in 2022 increased by 95 abortion cases (56.5%) out of 168 pregnancies. The incidence of abortion remains high due to the prevalence of abortion among working mothers. The purpose of this study is to analyze the factors influencing the incidence of abortion at Imelda Pekerja Indonesia General Hospital in 2023. The research employs a mixed-methods approach with sequential explanatory design. The quantitative sample consists of 50 pregnant women who experienced abortions, using medical record data and total sampling method. The qualitative research involves 10 informants selected through purposive sampling. Quantitative data analysis includes univariate, bivariate, and multivariate analysis using Chi-Square and Multiple Linear Regression tests. Qualitative data analysis involves data reduction, data presentation, and conclusion drawing. Based on the Chi-Square test results, variables with a p- value < 0.05 indicate a significant relationship between age, parity, pregnancy interval, history of abortion, education level, occupation, and maternal disease history with the incidence of abortion. The Multiple Linear Regression test reveals that the most influential factor is the history of abortion, particularly incomplete abortion. Qualitative research results also show the influence of age, parity, pregnancy interval, history of abortion, education level, occupation, and maternal disease history on the incidence of abortion, with the most influential variable being the history of abortion, specifically incomplete abortion. The conclusion of this study is that there is a significant relationship between age, parity, pregnancy interval, history of abortion, education level, occupation, and maternal disease history with the incidence of abortion at Imelda Pekerja Indonesia General Hospital in 2023, with the most influential variable being the history of abortion, particularly incomplete abortion. It is recommended that healthcare providers offer information about abortion to pregnant women, those who have experienced abortion, and those with a history of abortion, and encourage pregnant women to regularly undergo prenatal check-ups.